Prevalence and Associated Depression Risk Factors in Patients with Chronic Obstructive Pulmonary Disease in Qazvin, Iran (2014) - Zohal, Mohammadali; Mohammadi, Leili; Shamloo, Farhad; Javadi, Amir; Yazdi, Zohreh (European Journal of Therapeutics, 2023)
Objective: The prevalence of depression in patients with chronic obstructive pulmonary disease (COPD) varies from country to country, and even across various geographic regions within a country. The aim of this study was to determine the prevalence of depression and its related risk factors in patients with COPD in Qazvin, Iran. Methods: This cross-sectional study included 100 patients (34–80 years old) with COPD, referred to the pulmonary diseases clinic in Qazvin, Iran, during 2014. Demographics, medical records, current symptoms, and results of the lung function tests of the participants were recorded. Moreover, the pulmonary function was evaluated. COPD was categorized according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) system. The Beck depression inventory (BDI) was completed by all participants. Data were analyzed using the independent samples t-test, chi-squared test, and linear regression analysis. Results: Of the 100 patients with COPD, 90 were male. The mean age was 57.57±14.06 years. Moreover, among the 100 patients with COPD, 75 had depression. 67% had symptoms of mild to moderate depression, and only 8% had severe depressive symptoms. There was a significant association between depression and independent variables of cigaret smoking (β, 0.384; p<0.05), body mass index (BMI; β, −0.383; p<0.05), and one-second forced expiratory volume (FEV1; β, −0.264; p<0.05). Conclusion: The prevalence of depression in patients with COPD was high in this study. Smoking, BMI, and FEV1 were associated with depression. Effective interventions should be developed to address this clinical concern.